The history of matura exam in reflection of teaching English - Kelemenné Gerbovits, Szilvia; Gyöngyösiné Szabó, Judit (Acta Scientiarum Socialium, 2014)
The history of matura exam in reflection of teaching English The structure and the whole procedure of matura exam before 2005 was illogical and inconsistent. It did not and could not measure the relevant knowledge. The situation changed in 2005 with the introduction of the new, 2-level matura exam. Not only has it changed the whole exam procedures, but it has also affected (positively) the classroom work, the attitudes, methods of teachers, the way of feedback, and also the contents and style of coursebooks and other supplement materials. The study focuses especially on the past and current situation of foreign languages; and it also publishes the analysis of the 2013 matura exam measurement taken in Kaposvári Táncsics Mihály Grammar School.
Keywords: reasons for the matura exam; the two levels; standardization; international tendencies; the status of foreign languages; analysis of the 2013 matura exam